CAN EDUCATION INCREASE NHI MEMBERSHIP? A CASE STUDY AMONG MADURESE IN INDONESIA - Laksono, Agung Dwi; Wulandari, Ratna Dwi; Nandini, Nurhasmadiar; Santi, Maya Weka (Universitas Airlangga, 2025)
Background: Madura Island is often left behind in health development in East Java Province, including in the health sector. Poverty and poor education dominate this region. Aims: The research examined the role of education in National Health Insurance (NHI) membership among Indonesian Madurese. Methods: The study employed 791 respondents. We used NHI membership as an outcome variable, education level as an exposure variable, and seven control variables: regency, residence, gender, employment, age, wealth, and marital status. In the last stage, we employed a binary logistic test. Results: The results showed that 58.2% of Madurese people in Indonesia are members of the NHI. Regarding education level, Madurese with primary education was 1.672 times more likely than those without formal education to be an NHI member (95% CI 1.662-1.683). Meanwhile, Madurese with secondary education was 2.329 times higher than those uneducated to be an NHI member (95% CI 2.306-2.352). Moreover, Madurese with higher education was 4.593 times more likely to be an NHI member than uneducated Madurese (95% CI 4.517-4.669). Conclusions: Education level was associated with NHI membership among Madurese in Indonesia. The higher the education level, the higher the possibility of being an NHI member. Keywords: health insurance, National Health Insurance, Madurese, big data, public health